1980
DOI: 10.3168/jds.s0022-0302(80)83049-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Magnesium, Potassium, Glucose, and Immunoreactive Insulin Changes in Cows Moved Abruptly from Barn Feeding to Early Spring Pasture

Abstract: Cations and immunoreactive insulin in plasma were measured in 35 lactating cows moved abruptly to early spring pasture. After change of cows from grass-clover hay to fescue-bluegrass pasture containing 22 to 31 g potassium/kg dry matter, immunoreactive insulin of 5 Holstein cows increased 30% in 5 days and averaged 45% above prepasture concentrations for 40 days. Magnesium averaged 44% below prepasture content of plasma during this period and was correlated negatively with potassium -.17 and immunoreactive ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…However, the reduction in plasma Mg at dry-off was modest, and none of the cows were hypomagnesemic. It is possible that the negative effects on Mg absorption were counteracted by the reduced insulin level in plasma (Miller et al, 1980) and reduced ruminal fluid NH 4 + (Martens et al, 1988). The Mg concentration was lower in primiparous cows than in older cows, but the reason for this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction in plasma Mg at dry-off was modest, and none of the cows were hypomagnesemic. It is possible that the negative effects on Mg absorption were counteracted by the reduced insulin level in plasma (Miller et al, 1980) and reduced ruminal fluid NH 4 + (Martens et al, 1988). The Mg concentration was lower in primiparous cows than in older cows, but the reason for this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies with beef cows have shown that energy supplementation was less effective in maintaining serum Mg than MgO supplementation was. Miller et al (1980) compared beef cows abruptly placed on rye-wheat pasture supplemented with either 30 g MgO/d by capsule or 2.3 kg cornmeal/d. Both supplemented groups of cows had higher plasma Mg than unsupplemented controls for the first 10 d on pasture.…”
Section: Other Dietary Management Factorsmentioning
confidence: 99%
“…adrenaline, decrease plasma magnesium level. Increases in insulin levels in plasma are also associated with decreases in the concentration of plasma magnesium, and the rapid change in plasma magnesium level has been suggested to be caused by movements of magnesium ions from the plasma to the cells [87]. Clinical hypomagnesaemia, in contrast to milk fever, also occurs in beef cows and, as it is associated with dietary factors and sometimes external stressors, it may affect several cows in a herd at the same time [88].…”
Section: Diagnosing Grass Tetanymentioning
confidence: 99%